Performance analysis of vegetable and fruit promotion council Keralam (VFPCK) - Sayooj V (Department of Agricultural Extension, College of Horticulture, 2013)
Vegetable and Fruit Promotion Council, Keralam (VFPCK) was established in the state to bring many fold improvements in the field production and marketing of fruits and vegetables employing the farmer participatory approach through Self Help Groups(SHGs). The SHGs are the back bone of VFPCK. SHGs are groups of farmers with identified common objectives, tasks, group identities and neighbourhoods. The Council is moulding the SHGs as the basic level institutional units for introducing innovative intervention in horticulture. VFPCK has a different approach in extension management in comparison to the traditional extension system mainly followed by State Department of Agriculture. It has its unique and own management approach with a participatory and intimate style. Hence a study becomes very important to analyse the managing / coaching for performance improvement of SHG farmers. The research programme was designed to study the performance of the Self Help Groups of the VFPCK with a view to suggest measures for improvement of the work efficiency. The main objective was to study the managing / coaching for performance improvement of SHG farmers. The study aimed to delineate the reward and recognition activities prevailing in the Organisation. It was also envisaged to conduct a detailed case documentation with a built in SWOC analysis on a model Swasraya Karshaka Samithi (SKS) Finally, the study aimed to suggest suitable policy measures for improvement of the work efficiency of VFPCK. The study was limited to three districts of Kerala viz., Thrissur, Palakkad and Ernakulam. There were two categories of respondents. Ninety six farmers (36 master farmers and 60 beneficiary farmers) and 29 Assistant Managers constituted the samples. The data were collected using separate pre-structured and pre-tested interview schedules. The case analysis of the model Swasraya Karshaka Samithi (SKS) was done in Anappara SKS at Chalakkudi for which focussed group workshop was employed. Analytical tools such as Percentage analysis and Kendal’s coefficient of concordance were used. The performance rating of Self Help Groups of VFPCK was observed to be 74.04, which shows 74 per cent effectiveness in performance. The performance of SHGs was found to be comparatively good in terms of ‘regularity of SHG meetings’ 132 (80.97), ‘knowledge of farmers in vegetable / banana cultivation’ (78.71) and group cohesiveness (76.57). The performance rating of service support from VFPCK was found to be 78.20 per cent. High performance rating was registered for ‘increased marketing facility’ (89.50) followed by ‘accessibility to credit’ (79.30). Further, majority of the farmers changed from partial to full adoption of technologies in banana and vegetable cultivation in most of the agricultural practices. There was 60.13 per cent rating for the socioeconomic empowerment of farmers brought about by VFPCK. The socio-economic empowerment was comparatively high in the case of ‘increased income from agriculture’ (71.52% rating) followed by ‘increased social participation’ (69.77% rating), where as it was the lowest in the case of ‘increased savings’ with a rating of 33.65 per cent only. The performance rating of the coaching support to farmers by Assistant Managers was observed to be 78.11 per cent. However, the farmers (52.20 %) rated the farmer motivational practices in VFPCK as poor. There was 61.97 per cent rating for the employee motivational measures in VFPCK, where in the ‘performance appraisal’ measures were rated high (70.68%) and the promotional opportunity was rated as low (53.16 %). The recognition and respect the Assistant Managers get from farmers was perceived as the most satisfying item with a rating of 80.68 per cent. However, the Assistant Managers were least satisfied because of the present job insecurity. The case analysis done in Anappara SKS at Chalakkudi revealed that active SHGs, farmers involved in commercial cultivation, elimination of middle men, and increased bargaining power are its strengths. Lack of enough storage facility was the only major weakness the SKS had. Many measures like proper provision of storage and processing facilities in all the SKSs, measures to improve farmer and group recognition based on performance, and redefining area of operation for Assistant Managers for enhancing efficiency of operation are required at policy level to improve the effectiveness of VFPCK